Elephant-Train Conflicts in Tamil Nadu and Related Safety Measures: A Study - R.Vasanth, Dr.A.Pandian (International Journal of Advanced Science and Technology, 2020)
Indian Railway network has extensive cut over numerous forestry landscapes over geographical regions in India. It seems to be a main cause of train collision with many wildlife species which includes mammals like elephants. Specifically, railway lines cross elephant territory in numerous states like Tamil Nadu, West Bengal and so on. This results in death of approximately 200 elephants from 80’s to 15. As 54 km Coimbatore-Palakkad track in Tamil Nadu witnesses Elephant – Train collisions very often. Here, an extensive study was done with an aim to map locations of collision and to produce a vulnerability map to depict locations that are prone towards accidents. Here, elephant movement region and elephant crossing points over railway tracks are monitored for mapping and provided as accident locations. Based on various online available resources, elephant-train collision over these lines is analysed in Tamil Nadu specifically in Hosur and Coimbatore region. It is identified that there are numerous hotspot locations where collision and deaths were focussed. However, some inconsistent number of accidents occurs during night time. Elephant-Train accidents and crop cultivation seems to be closely related to one another in Tamil Nadu. During cultivation season, probability of increased elephant movement near and over railway lines is higher. However, Male elephants are considered to be much prone towards accidents as they possess more harsh behavioural characteristics which leads them to cross the tracks more often. So as to reduce consistency of accidents in these regions, some suggestions are provided like train speed reduction, reducing train operations during night time, providing underpasses and overpasses with recent technologies, virtual fencing concept, track re-alignment and track fencing and so on. This study helps in reduction of accidents and to provide place for wildlife to sustain over earth. Keywords- Elephant-Train collision, Indian Railways, accident probability, virtual fencing, accident consistency.